Novel objects placed in feeder increase the feeding time of foals fed concentrate feed - Brandi, Roberta Ariboni; Medeiros, Mayra Oliveira; Brandi, Laura Alves; Nunes, Tamires Romão; Nicolau, Lívia Vieira Costa; Correa, Graziani Ferrer; Ribeiro, Leonir Bueno; Titto, Cristiane Gonçalves (Acta Scientiarum. Animal Sciences, 2024)
This study aimed to evaluate the feeding time and reactivity of male and female foals exposed to novel objects (seven plastic balls measuring 8 cm in diameter) placed inside the feeder. Eleven mixed-breed foals (males = 6; 316 ± 42 kg of BW, females = 5; 290 ± 35 kg of BW) were used. The amount of concentrate feed was calculated using 2000 g kg-1 BW for males and 1500 g kg-1 BW for females. Behavioral variables were assessed using a scoring system. Data on time spent feeding were subjected to analysis of variance and regression analysis (p < 0.05) and compared using the PROC REG procedure of SAS (with object = without object). A line of equality (y = x) was used to test correlations. The behavioral model was fitted by a generalized linear model using the GLIMMIX procedure of SAS, and means were compared (p < 0.05) by t-tests. Feeding time differed between sexes (males = 23.7 ± 4.8 min., females = 19.5 ± 3.1 min.), attributed to the longer time spent by males in attentive behavior when plastic balls were placed in the feeders. There was no effect on composite behavioral score. Both males (18.37%) and females (14.29%) were classified as calm while feeding in feeders with unfamiliar objects. By adding plastic balls to the feeder, it was possible to increase the feeding time of foals fed concentrate feed.